A qualitative study on perceptions of doping induction factors among elite athletes - Hibino, M.; Funahashi, H.; Ishii, T. (Japan Journal of Physical Education, Health and Sport Sciences, 2020)
Understanding the causes of doping behavior in athletes has been a core research topic in the antidoping literature. The present study was an attempt to qualitatively explore perceptions of factors that influence athletes and prompt them to take part in doping. The subjects were 12 Japanese elite athletes and a thematic approach was used to analyze the data obtained from a semi-structured interview. Three main factors were revealed: personal, socio-environmental, and situational. The perceived personal factor comprised 3 sub-themes: `immoral stance`, `extrinsic motivation`, and `ego orientation`. The perceived socio-environmental factor comprised 9 sub-themes, including `entourage`, `doping by other athletes`, `social norms`, etc. The perceived situational factor comprised 6 sub-themes, including `important competition`, `performance decline`, `injury`, etc. Several interactions between these factors were observed, suggesting directions for future research. These findings will be of help for developing evidence-based preventive measures against doping.